Radially polarized beams for surface plasmon microscopy - Moh, Jonathan Kenjin. (2010)
Radial polarised (RP) light is a uniquely polarised light pattern whose distribution of the electric field vectors is arranged radially around the optic axis of a laser beam. The spatial distribution of the electric field vectors in RP beams bestows unique capabilities in various applications, making them the optimal polarization of choice when properly applied in areas like laser material processing, avoiding detrimental thermal effects in high power laser systems and high e-field confinement of light. However it is perhaps in the field of scanning microscopy that RP light holds exceptional promise to improve or even revolutionize. Radial polarized beams open an entirely new chapter of study directed towards the influence of vectorial polarization in the focus fields of scanning optical microscopy. This is an added dimension to the existing aspects that have been studied for practical scanning microscopy such as effective numerical aperture, pulse width, wavelength, laser power, etc. The work contained in this thesis is directed towards the practical generation of RP light and its novel application to a virtual probe imaging technique for investigating the surface contact regions of biological specimens in a sealed environment. The thesis first discusses the principle of generating RP light from an initial linear polarized source by polarization conversion through the selective sampling of circularly polarized OV beams (a light field with a twisted or helical wavefront structure). Compared to alternative RP generation techniques, the technique here is compact, relatively easier to implement and may be directly implemented to a wide range of existing lasers (with no modifications to the internal workings of the systems) in both the continuous wave and nonlinear regime.